Development and validation of an instrument to measure expectancy for success and subjective task value constructs in the context of higher education (Journal of Applied Learning and Teaching, 2024)
Given the relevance of the Expectancy Value Theory in the context of higher education, the aim of this study was to develop and validate an instrument to measure the constructs within this framework at the higher education level. Undergraduate students (n = 565) from one of the largest private higher education institutions in Singapore were surveyed online using two versions (a 20-item and a 16-item version) of the Expectancies and Values in Higher Education Instrument (EVHEI). Exploratory factor analyses using a subsample of the cohort yielded two alternative versions of the instrument (a five-factor and a four-factor version). Both were subsequently validated using confirmatory factor analysis on data from the other subsample.  The study results suggest that the EVHEI holds considerable promise for measuring motivation-related constructs at the higher education level. Keywords: Higher education, Expectancy Value Theory, instrument development, expectancy for success, subjective task value